PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA MAGISTER MANAJEMEN UNIVERSITAS TRISAKTI - Pratomo, Regas Panji (Manajerial dan Bisnis Tanjungpinang, 2025)
The problem of this research is to analyze the situation of financial literacy and financial behavior related to consumptive behavior. The purpose of this research is to know the effect of financial literacy and financial behavior to consumer behavior students at Trisakti University. The methodology in this study is obtaining primary data by distributing 110 questionaires among the Master’s Students at Trisakti University in 2017.There are 104 questionaires returned. The data have been collected and processed by using SPSS version 21 for validity, reability, and descriptive tests. Furthermore, Lisrel version 8.71 is used to apply SEM method. This study is expected to contribute empirical evidence about graduate student’s consumptive behavior related to financial knowledge. Students can utilize it to improve their financial behavior, it apply. Moreover, further research can be applied by continuing these results. The limitations of this study are (1) the samples are graduate students at Trisakti University in 2017 only, (2) applying panel data analysis units Structure Equation Model (SEM) through Lisrel package program. This research implies that improving financial literacy and understanding future risk, saving and loans are necessary.